Improving the nonlinear energy conversion efficiency of a Kerr-comb-based broadband multi-wavelength light source by introducing an optical feedback loop. (28th April 2017) - Lei, Xun; Chen, Shaowu; Zhang, Libin
Abstract: We simulate the generation of microcavity solitons in Kerr combs, evaluate their characteristics in the frequency domain via the Lugiato–Lefever equation (LLE), and optimize their shapes in the time domain by changing some related parameters to flatten the spectrum of the optical frequency combs and improve the nonlinear energy conversion efficiency of the underlying four-wave mixing process. In addition, we propose a new Kerr comb generation scheme to obtain an energy-efficient multi-wavelength light source by introducing an optical feedback loop with phase control in the pumping system. The simulation results show that the proposed scheme can enhance the nonlinear energy conversion efficiency of the multi-wavelength source and reduce the pump power level by about 32%.